Primary control reserve of electric power by feedwater flow rate change through an additional economizer – A case study of the thermal power plant "Nikola Tesla B". (15th March 2018) - Stevanovic, Vladimir D.; Ilic, Milica; Djurovic, Zeljko; Wala, Tadeusz; Muszynski, Slawomir; Gajic, Ivan
Abstract: Coal-fired thermal power plants (TPPs) had been generally designed to cover base loads of electricity consumption. Nowadays, they should be flexible to participate in the primary frequency control of electric system, especially because of increased number of wind and solar plants with intermittent electricity production. In this paper a new method for the primary power control in TPPs is presented, based on the feedwater flow rate changes between the feedwater heaters (FWHs) and an additional high pressure economizer. The achieved primary power control reserve is demonstrated by measurements at the lignite-fired 650 MWe TPP after its retrofit by the installation of the high pressure economizer in parallel with FWHs. In addition, the TPP transient operation during the primary control are simulated and analyzed with the developed thermal-hydraulic model of the steam turbine heat regeneration system. The control reserve of approximately 10 MWe is shown both by measured data and results of numerical simulations. The control reserve is originally provided by the fresh steam throttling in front of the turbine, but this throttling can be reduced by the application of the new method. The rates of change of wall temperatures of FWHs tubes are within allowed limits during the transients. Highlights: A high pressure economizer was installed at the coal-fired 650 MWe power plant. The economizer is in parallel with feedwater heaters. Feedwater flow change through the economizer enables the primary power control. Measurements and numerical simulations show 10 MWe of primary control reserve. The primary control by the economizer reduces a need for the fresh steam throttling.